2006
DOI: 10.1038/sj.mp.4001802
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of adult hippocampal neurogenesis by thyroid hormones: implications in depressive-like behavior

Abstract: Hormonal imbalances are involved in many of the age-related pathologies, as neurodegenerative and psychiatric diseases. Specifically, thyroid state alterations in the adult are related to psychological changes and mood disorders as depression. The dentate gyrus of the hippocampal formation undergoes neurogenesis in adult mammals including humans. Recent evidence suggests that depressive disorders and their treatment are tightly related to the number of newly born neurons in the dentate gyrus. We have studied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
142
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(156 citation statements)
references
References 69 publications
(89 reference statements)
8
142
2
Order By: Relevance
“…For example, agomelatine, a new antidepressant that acts as a melatonin agonist, also stimulates neurogenesis in rat hippocampus, 87 as do thyroid hormones, which have been used in the treatment of depression. 47 Psychotropic drugs that do not have antidepressant activity, such as haloperidol, have no effect on neurogenesis. 85 Thus, the induction of adult neurogenesis might represent a common final target for different classes of antidepressants.…”
Section: © 2 0 0 8 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, agomelatine, a new antidepressant that acts as a melatonin agonist, also stimulates neurogenesis in rat hippocampus, 87 as do thyroid hormones, which have been used in the treatment of depression. 47 Psychotropic drugs that do not have antidepressant activity, such as haloperidol, have no effect on neurogenesis. 85 Thus, the induction of adult neurogenesis might represent a common final target for different classes of antidepressants.…”
Section: © 2 0 0 8 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%
“…46 Corticosteroids were the first hormones found to have an affect on hippocampal neurogenesis. 41 Activation of hypothalamic-pituitary-adrenal axis and sustained elevation of glucocorticoids can lead to chronic inhibition of neurogenesis, 47 whereas adrenalectomy leads to an increase in the number of neurons in the adult rat hippocampus. 48 Thyroid hormones also stimulate neurogenesis.…”
Section: Regulation Of Adult Neurogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…However, only in CA1 the total 50 number of pyramidal neurons was reduced by adult hypothy-51 roidism [26]. Nevertheless, Alva-Sánchez et al [27] found that short-term adult-onset hypothyroidism impairs 56 dendritic arborization of immature neurons.…”
mentioning
confidence: 99%
“…Thyroid hormones: Thyroid hormones (TH) imbalances are implicated in the pathophysiology of neurodegenerative and psychiatric conditions. These hormones are very essential for brain development, maturation and have been shown to promote neurogenesis, in particular, in the hippocampus [59]. Hypothyroidism has been linked to depressive -like behavior in that it impaired hippocampal neurogenesis which resolved with hormone replacement.…”
Section: G) Hormones and Depressionmentioning
confidence: 99%